Biochar as substrate conditioner for the production of seedling of native forest species (Research, Society and Development, 2023)
The practice of mixing or combining substrates of different origins is common in nurseries, and the use of biochars is a way to improve the composition of the substrate, meet the particularities of the plant, reduce production costs, and re-signify materials that would be discarded in the environment. This work had the objective of verifying the influence of the use of biochar in the production of seedlings of woody species, indicating the doses and composition of substrates that best adjust to the production of quality seedlings. In a literature review of the last ten years, we sought to verify the recommended doses and the effects of biochar on substrate composition. In the literature, the potential use of biochar as a substrate component was verified, mainly because it has a porous and reactive structure, capable of increasing the availability of water and other nutrients for the plant and being a shelter for several beneficial microorganisms. The appropriate dose of biochar in the substrate composition may vary according to the species of interest, management system, source and proportions of inputs. Thus, it is concluded that different sources of inputs, combinations and proportions between them, affect the production of seedlings in different ways, with the best dose of biochar being a complex matter and of notable importance when the objective is to produce seedlings with quality.